Periconceptional risk factors of spina bifida among Egyptian population: a case–control study. (17th July 2016) - Maged, Ahmed; Elsherbini, Moutaz; Ramadan, Wafaa; Elkomy, Rasha; Helal, Omneya; Hatem, Dina; Fouad, Mona; Gaafar, Hassan
Abstract: Objective : To study the preconceptual & early conceptional risk factors predisposing to the development of spina bifida (SB) among Egyptian population. Study design : The study involved 197 pregnant women undergoing fetal anatomy scan; 97 women proved to have fetal SB and 100 women with normal fetuses as a control group. The control group was recruited randomly in the same period from patients undergoing anatomical scan. Risk factors that might lead to SB were investigated including maternal age, gravidity, parity, residence, history of diabetes mellitus or drug intake, smoking, infections, exposure to X-ray, history of congenital anomalies in other offspring, parental consanguinity, positive family history, and folate supplementations. Results : SB affected the lumbo-sacral region in the majority of cases (89.7%). It was associated with hydrocephalus in 66 cases (68%), polyhydramnios in 12 cases (12.4%). The SB group showed significantly higher parity ( p  = 0.005), more frequent history of drug intake ( p  < 0.001), higher frequency of infection with CMV ( p  = 0.004), and HSV ( p  = 0.013) and less proportion of folate supplementation ( p  < 0.001). Conclusion : The rate of SB in the tested group was five per 1000. Risk factors were lack of folate supplementation and history of antiepileptic drugs intake.